2019
DOI: 10.1002/jlb.1ma1019-186r
|View full text |Cite|
|
Sign up to set email alerts
|

Concomitant deletion of SLAM-family receptors, NKG2D and DNAM-1 reveals gene redundancy of NK cell activating receptors in NK cell development and education

Abstract: NK cells recognize “unwanted” cells using a variety of germline‐encoded activating receptors, such as the seven members of signaling lymphocyte activating molecule (SLAM)‐family receptors (SFRs), natural killer cell group 2D (NKG2D), and DNAX accessory molecule‐1(DNAM‐1). Whether these receptors redundantly or synergistically regulate NK cell development and effector function remains poorly understood. By generating mice lacking SFRs, NKG2D, and DNAM‐1, separately or in combination, we found that SLAMF6, one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The activating signal is potentially mediated by one or more known activation receptors or a yet unidentified receptor. Recent efforts have shown that missing-self is functional in mice deficient in SLAM family members and/or NKG2D [95][96][97]. Unraveling the activation receptor(s) involved in missing-self is key to fundamentally understand antiviral NK cell immunity and has implications for antitumor NK cell immunity as well.…”
Section: Missing-self In Antiviral Immunitymentioning
confidence: 99%
“…The activating signal is potentially mediated by one or more known activation receptors or a yet unidentified receptor. Recent efforts have shown that missing-self is functional in mice deficient in SLAM family members and/or NKG2D [95][96][97]. Unraveling the activation receptor(s) involved in missing-self is key to fundamentally understand antiviral NK cell immunity and has implications for antitumor NK cell immunity as well.…”
Section: Missing-self In Antiviral Immunitymentioning
confidence: 99%